PATIENTS' KNOWLEDGE AND ATTITUDES TOWARDS INFECTION CONTROL IN THE DENTAL PRACTICE - Lucia BARLEAN; Ioan DANILA; Cristina DASCALU; Ciprian MERIUTA (Romanian Dental Association for Education, 2013)
Objectiv: This study aims to investigate patients concern and knowledge regarding the cross-infection risk and the infection control methods in the dental practice. Material and methods: The questionnaire-based survey was conducted among 170 patients aged 16 to 68 years. The questionnaire included 20 items related to the medical staff protection equipment, dentist professional appearance and safety protocols in the dental practice. The patients' answers were analyzed by gender, age and education level. using the SPSS 15.0 statistical package and levels of statistical significance were set at p<0.05. Results: The results revealed that 83,6% of the patients have confidence that the medical staff protects them from catching general illnesses during dental treatment.45,5% of the patients are concerned about the procedures used by the dentist to control cross-infection. Positive responses were associated with traditional professional clothing as the white coat and the name tag. 89,0% of the patients want the dentists to wear rubber gloves, 63,6% agree to face masks and 47,2% to protective eye glasses. Conclusions: The results of the present study prove that most patients trust the dentist in the matter of infection control protocols adopted in the dental office but they claim a better approach in this domain. The medical team has the responsibility to inform the patient on the measures which have been taken to reduce the risk of infection, in order to increase the public confidence in dental care safety.